Immunothrombotic Activity of Damage-Associated Molecular Patterns and Extracellular Vesicles in Secondary Organ Failure Induced by Trauma and Sterile Insults - Eppensteiner, John; Davis, Robert Patrick; Barbas, Andrew S.; Kwun, Jean; Lee, Jaewoo (Frontiers in Immunology, 2018)
Despite significant improvements in injury prevention and emergency response, injury-related death and morbidity continues to increase in the US and worldwide. Patients with trauma, invasive operations, anti-cancer treatment, and organ transplantation produce a host of danger signals and high levels of pro-inflammatory and pro-thrombotic mediators, such as damage-associated molecular patterns (DAMPs) and extracellular vesicles (EVs). DAMPs (e.g., nucleic acids, histone, high-mobility group box 1 protein, S100) are molecules released from injured, stressed, or activated cells that act as endogenous ligands of innate immune receptors, whereas EVs (e.g., microparticle, exosome) are membranous vesicles budding off from plasma membranes and act as messengers between cells. DAMPs and EVs can stimulate multiple innate immune signaling pathways and coagulation cascades, and uncontrolled DAMP and EV production causes systemic inflammatory and thrombotic complications and secondary organ failure. Thus, DAMPs and EVs represent potential therapeutic targets and diagnostic biomarkers for secondary organ failure. High plasma levels of DAMPs and EVs have been positively correlated with mortality and morbidity of patients or animals with trauma or surgical insults. Blocking or neutralizing DAMPs using antibodies or small molecules has been demonstrated to ameliorate sepsis and secondary organ failure in animal models. Furthermore, a membrane immobilized with nucleic acid-binding polymers captured and removed multiple DAMPs and EVs from extracellular fluids, thereby preventing the onset of DAMP- and EV-induced inflammatory and thrombotic complications in vitro and in vivo. In this review, we will summarize the current state of knowledge of DAMPs, EVs, and secondary organ failure, and we will discuss potential therapeutics and preventive intervention for organ failure secondary to trauma, surgery, anti-cancer therapy, and allogeneic transplantation.